Peran Customer Review dan Rating Produk dalam Membangun Kepercayaan Konsumen pada Platform TikTok Shop - Azzahro, Amalia Fasya; Lida, Ulfah Mey (Jurnal Ekonomi dan Bisnis Islam, 2026)
AbstractThe development of social commerce through platforms such as TikTok Shop has encouraged changes in consumer behavior in conducting online purchasing activities. In this context, information generated by other consumers, such as customer reviews and product ratings, has become an important reference in building consumer trust. This study aims to analyze the effect of customer reviews and product ratings on consumer trust in purchasing fashion shirt products through TikTok Shop among the Kudus community. This research employs a quantitative approach with an associative research design. The sampling technique used is non-probability sampling with a purposive sampling method involving 100 respondents who have experience using TikTok Shop. Data were collected through an online questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 20. The results indicate that customer reviews do not have a significant effect on consumer trust, while product ratings have a positive and significant effect on consumer trust. Therefore, product ratings are considered a more dominant factor in shaping consumer trust in transactions on the TikTok Shop platform.Keywords: Customer Review; Product Rating; Consumer Trust; TikTok Shop. AbstrakPerkembangan social commerce melalui platform TikTok Shop mendorong perubahan perilaku konsumen dalam melakukan pembelian produk secara daring. Dalam kondisi tersebut, informasi yang berasal dari konsumen lain seperti customer review dan rating produk menjadi salah satu referensi penting dalam membangun kepercayaan konsumen. Penelitian ini bertujuan untuk menganalisis pengaruh customer review dan rating produk terhadap kepercayaan konsumen pada pembelian produk fashion kemeja di TikTok Shop pada masyarakat Kudus. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian asosiatif. Teknik pengambilan sampel menggunakan non-probability sampling dengan metode purposive sampling terhadap 100 responden yang pernah menggunakan TikTok Shop. Data dikumpulkan melalui kuesioner daring dan dianalisis menggunakan regresi linier berganda dengan bantuan SPSS versi 20. Hasil penelitian menunjukkan bahwa customer review tidak berpengaruh signifikan terhadap kepercayaan konsumen, sedangkan rating produk berpengaruh positif dan signifikan terhadap kepercayaan konsumen. Dengan demikian rating produk menjadi faktor yang lebih dominan dalam membentuk kepercayaan konsumen dalam transaksi pada platform TikTok Shop.Kata Kunci: Customer Review; Rating Produk; Kepercayaan Konsumen;  TikTok Shop.